An Analysis of the Translation Methods of Edgar Allan Poe's Short Story 'The Tell-Tale Heart' Based on Newmark's Theory - Putri Yulitha, Noviyanti Dwianisa (Smart Edu Center, 2024)
This research analyses the translation methods used by Harum Wibowo in translating Edgar Allan Poe's short story